Biarticular elements as a contributor to energy efficiency: biomechanical review and application in bio-inspired robotics. (8th November 2017) - Junius, Karen; Moltedo, Marta; Cherelle, Pierre; Rodriguez-Guerrero, Carlos; Vanderborght, Bram; Lefeber, Dirk
Abstract: Despite the increased interest in exoskeleton research in the last decades, not much progress has been made on the successful reduction of user effort. In humans, biarticular elements have been identified as one of the reasons for the energy economy of locomotion. This document gives an extensive literature overview concerning the function of biarticular muscles in human beings. The exact role of these muscles in the efficiency of human locomotion is reduced to three elementary functions: energy transfer towards distal joints, efficient control of output force direction and double joint actuation. This information is used to give an insight in the application of biarticular elements in bio-inspired robotics, i.e. bipedal robots, exoskeletons, robotic manipulators and prostheses. Additionally, an attempt is made to find an answer on the question whether the biarticular property leads to a unique contribution to energy efficiency of locomotion, unachievable by mono-articular alternatives. This knowledge is then further utilised to indicate how biarticular actuation of exoskeletons can contribute to an increased performance in reducing user effort.